Unutulmuş Tedaviler - Hürsoy, Nur; Gün, Hamide Betül; Aşık Özdemir, Vacide; Akbal, Yağmur; Aktürk Acar, Filiz; Kılıç, Hülya; Topçu, Atilla; Tekeoğlu, Uğur; Hocaoğlu, Çiçek; Kanat, Ayhan; Durmaz, Serdar; Okumuş, Burak; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-